Pengaruh Kondisi Lingkungan Permukiman Terhadap Kualitas Air Tanah Di Kecamatan Pasar Kliwon Kota Surakarta - Saktiyawan, Saktiyawan; , Dra. Alif Noor Anna, M.Si; , Drs. Munawar Cholil, M.Si (2016)
This study discusses the influence of environmental conditions on the quality of groundwater settlement that aims to 1) determine the distribution of groundwater quality based on the density of the settlements in the study area 2) comparing the difference in the quality of ground water with drinking water quality standards. The method used in this study is a survey method, whereas the determination of sampling areas purporsive sampling method. It's been based on considerations density settlements, while in sampling in the study area using the classification level of density settlements are divided into five classes. Research analysis using comparative description by comparing the quality of ground water with drinking water quality standards. The data used in this study are primary data and secondary data, the primary data is the result of laboratory consisting of chemical and physical parameters of the groundwater, while secondary data, population density data. From the research, the study area have groundwater quality criteria are divided into two classes, namely the groundwater quality is good and less good. Good quality ground water contained in the three regions and two areas that have poor quality. Of the five regions in the study area groundwater can still be used for drinking water purposes in accordance with the provisions of Minister Regulation Number 492 Year 2010 only, there are two areas that have a physical parameter value is the color and turbidity greater than any other region